Social Justice Drives Students Deeper: A Statistics Lesson on Wealth Impacting Quality of Life - Wall, Mackenzie (Ohio Journal of School Mathematics, 2017)
This article communicates the value in teaching for social justice in a mathematics classroom. A lesson is provided with the intent of empowering students to reach statistically sound conclusions that hold weight and change their perspectives through the vehicle of social justice. The lesson involves students investigating whether wealth has an impact on quality of life. We, as teachers, don’t need to keep trying to make our students care about statistical concepts, their craving for justice will do that for us if we let them tap into it through real, compelling data.